(untitled) (Ukrainian Journal of Ophthalmology, 2026)
ransillumination of the eye through the cornea or sclera allows observation of shadows in projections of intraocular structures on sclera. Purpose. To study the possibilities of near-infrared radiation using to visualize ciliary body structures by transpalpebral transillumination. Material and Methods. There were 15 people (30 eyes) with no visible lesions of the anterior segment of the eye; 20 patients (20 eyes) with terminal glaucoma before laser transscleral ciliary body destruction; 15 patients (15 eyes) with intraocular tumors located in the ciliary body; 5 isolated eyes with intraocular melanoma. In all cases a colour photo of the anterior eye segment, infrared transillumination, ultrasound scan were made. Results. In all cases in healthy individuals by transpalpebral infrared eye transillumination ciliary body and its structures was registered. In patients with terminal glaucoma by infrared transillumination prior laser ciliary body destruction was visualized location of ciliary processes. In patients with intraocular tumors infrared transillumination made it possible to visualize tumor and to estimate its localization in relation to the ciliary body structures. In isolated eyes were registered dimensions of the ciliary body structures and the dimensions of their shadows on the sclera with transpalpebral infrared eye transillumination. Conclusion. Transpalpebral infrared eye transillumination provides imaging of the ciliary body and accurately estimates the projection of its structures to the sclera. Infrared transillumination can be used for visualization of the ciliary body in patients with terminal glaucoma prior laser transscleral ciliary body destruction. Infrared transillumination helps to visualize intraocular tumors and determine their projection on the sclera, which can be used for diagnostic purposes and during destruction of the tumor.